PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS APLIKASI GOOGLE SKETCH UP PADA MATERI SMA - Erninda Ruanti; Mohammad Fahthul Aziz; Komang Destiana Pratiwi; Putri Sasalia S.; Siti Dian Anugrah (Afore : Jurnal Pendidikan Matematika, 2025)
This study aims to develop a practical learning video media based on the Google SketchUp application for high school subjects. The research employs a Research and Development (R&D) method consisting of three main stages: defining, designing, and developing. In the defining stage, the researcher conducts a needs analysis and interviews with teachers, as well as analyzes the material in accordance with the applicable curriculum. The designing stage involves creating an engaging and systematic concept for the learning video using the Google SketchUp application, complemented by animations and other multimedia elements. The development stage involves producing the learning video product, which is then tested and validated by media experts and material experts. The research subjects consist of two media experts, two material experts, and 27 high school students who participate in a small group trial to measure the practicality of the developed media. Validation results show that the learning video received a 79% score from media experts, indicating that the media is feasible to use, and 81.53% from material experts, indicating that the media is highly feasible. Furthermore, the practicality test with students yielded a score of 87.74%, indicating that the media is very practical for use in the learning process. Based on these validation and practicality results, it can be concluded that the learning video media based on the Google SketchUp application is effective and feasible as a learning tool at the high school level. This media is expected to enhance students' understanding of the subject matter through a more engaging and interactive presentation.